As orientações da Organização Internacional do Trabalho (OIT) para a formação da força de trabalho da juventude no Brasil. - Batistussi, Bruno Cezar (2024)
Since the 1990s, the actions of International Organizations in Brazil and other countries in the periphery and semi-periphery of global capitalism have intensified. Consequently, entities linked to these Organizations began to concentrate their efforts on producing studies that could serve as practical elements for the realization of international agendas. Thus, the conduct and implementation of the economic, social, and educational policies of the Brazilian state began to be monitored and guided by such Organizations. The objective of this research was to understand the guidelines of the International Labour Organization (ILO), as an agency linked to the United Nations (UN), for the training of the youth workforce in Brazil. The research was conducted based on the ILO's database, through studies published between 2003 and 2022, focusing on publications that addressed the training agenda for the youth workforce, both considering Brazil as a specific region for study and through studies with general insights regarding the concepts of work, youth, workforce, and workforce training. Subsequently, considering the same temporal scope, a data survey was conducted to establish the concrete situation of Brazilian youth in economic, social, and educational terms. As a result, it was possible to perceive that the ILO, through its guidelines and proposals, sought to insert itself into the decision-making process of Brazilian policy, especially in areas related to work, employment, and the training of the youth workforce. Despite this, the ILO's diagnosis pointed to the ineffectiveness of the Brazilian educational system, leading this Organization (ILO) to advocate that the training of the youth workforce, at all levels and modalities, should align with the demands of the labor market.